Strategi Pengembangan Minuman Tradisonal Arak Bali Menggunakan Model Analisis SWOT Dan QSPM: Studi Kasus Desa Tri Eka Buana Karangasem Bali - Pranatayana, Ida Bagus Gde; Pratiwi Arcana, Komang Trisna (Metta : Jurnal Ilmu Multidisiplin, 2021)
Evaluating and offering strategies for the existence of traditional Balinese alcoholic drinks that have the potential as a tourist attraction in Tri Eka Buana Village, Sidemen, Karangasem is the main goal of this research. For this purpose, different data collection tools were used, namely through interviews and questionnaires given to the Bali Provincial Tourism Office, the Village Head, the Head of the Tourism Awareness Group, and the Head of the Arak Cooperative in the village. Evaluation of the influence of strengths, weaknesses, opportunities and threats (SWOT) as well as quantitative strategic planning matrix (QSPM) analysis techniques are used to identify the appropriate management strategy. The results showed that Balinese wine has the potential to be developed in the form of arak agro-tourism. Its development must involve the participation of local communities as stakeholders and shareholders. Arak agrotourism can be an alternative for arak farmers who are not willing to cooperate with alcoholic beverage management bodies to be marketed to the tourism industries. These tourism options play a role in improving the community's economy and have a sustainable impact on biodiversity.